Design of Integrated Electrical Installations with Solar Panel in Muhammadiyah Ibtidaiyah Madrasah Building in Jurangono, Gemantar Village, Mondokan-Sragen - Asyari, Hasyim; Sarjito, Sarjito; Mutiari, Dhani; Setyowati, Suryaning; Setiawan, Budi (Universitas Muhammadiyah Surakarta, 2023)
The Muhammadiyah Mondokan Branch Manager has a business charity in the field of education at the Elementary School level or often known as MI Muhammadiyah (MIM). MIM Gemantar was founded in 1978 with a basic education level. In carrying out its activities, MIM Gemantar is under the auspices of the Ministry of Religion. Accredited B on November 9, 2017. MIM Gemantar has the most apprehensive building conditions compared to the other four MIMs in Mondokan. On Monday, according to the news from Jateng, inews.id, it was reported that the roof of MI Muhammadiyah Gemantar had collapsed, resulting in the head of the school office and 2 students being injured. The incident of the collapse of the classroom roof occurred during teaching and learning activities or KBM taking place on Monday, January 9 2023 around 08.15 WIB. For the past four months, students from three classes have been assigned to one room. The room whose roof collapsed was used by three classes due to the small number of students, namely grades II, IV and VI. The purpose of this research is to design an integrated electrical installation with solar panels in the MIM Gemantar building which will be renovated. This has several benefits, including as a form of utilizing renewable energy and also as a learning medium for 4th year students with the theme of renewable energy. The method of this activity is for the team to obtain a floor plan of the building to be built, then carry out a design which is as simple as the implementation process, it is easy to update capacity, draw a single line and plan a budget. Currently the MIM Gemantar Mondokan Sragen building has finished building 4 classrooms, so it still requires the construction of 2 more classrooms. The source of electricity for the electrical installation of the 4 classroom buildings all use electrical energy from PLN. In the future, if funds are available and the manager wants the installation of solar panels, then only add according to the design results of a single line electrical installation that is integrated with solar panels on-grid (can be done in stages of 200 Wp, 400 Wp, even up to 1,000 Wp). The capacity of solar panels does not have to match the planned capacity, meaning that this capacity can be carried out in stages according to the conditions of the funds provided.